Functional and Pathogenic Roles of Retroviral Antisense Transcripts - Toyoda, Kosuke; Matsuoka, Masao (Frontiers in Immunology, 2022)
Exogenous retroviruses such as human immunodeficiency virus type 1 (HIV-1), human T-cell leukemia virus type 1 (HTLV-1) and bovine leukemia virus (BLV) can cause various diseases including immunodeficiency, inflammatory diseases and hematologic malignancies. These retroviruses persistently infect their hosts. Therefore, they need to evade host immune surveillance. One way in which these viruses might avoid immune detection is to utilize functional RNAs, rather than proteins, for certain activities, because RNAs are not recognized by the host immune system. HTLV-1 encodes the HTLV-1 bZIP factor (HBZ) gene in the antisense strand of the provirus. The HBZ protein is constantly expressed in HTLV-1 carriers and patients with adult T-cell leukemia-lymphoma, and it plays critical roles in pathogenesis. However, HBZ not only encodes this protein, but also functions as mRNA. Thus, HBZ gene mRNA is bifunctional. HIV-1 and BLV also encode long non-coding RNAs as antisense transcripts. In this review, we reshape our current understanding of how these antisense transcripts function and how they influence disease pathogenesis.